Hypoxia and Wnt signaling inversely regulate expression of chondroprotective molecule ANP32A in articular cartilage. Issue 4 (April 2023) - Quintiens, J.; De Roover, A.; Cornelis, F.M.F.; Escribano-Núñez, A.; Sermon, A.; Pazmino, S.; Monteagudo, S.; Lories, R.J.
Summary: Objectives: ANP32A is a key protector of cartilage health, via preventing oxidative stress and Wnt hyper-activation. We aimed to unravel how ANP32A is regulated in cartilage. Methods: A bioinformatics pipeline was applied to identify regulators of ANP32A . Pathways of interest were targeted to study their impact on ANP32A in in vitro cultures of the human chondrocyte C28/I2 cell-line and primary human articular chondrocytes (hACs) from up to five different donors, using Wnt-activator CHIR99021, hypoxia-mimetic IOX2 and a hypoxia chamber. ANP32A was evaluated using real-time quantitative polymerase chain reaction (RT-qPCR) and Western blot. In vivo, the effect of hypoxia was examined by immunohistochemistry in mice injected intra-articularly with IOX2 after destabilization of the medial meniscus. Effects of Wnt hyper-activation were investigated using Frzb -knockout mice and wild-type mice treated intra-articularly with CHIR99021. Wnt inhibition effects were assessed upon intra-articular injection of XAV939. Results: The hypoxia and Wnt signaling pathways were identified as networks controlling ANP32A expression. In vitro and in vivo experiments demonstrated increases in ANP32A upon hypoxic conditions (1.3-fold in hypoxia in C28/I2 cells with 95% confidence interval (CI) [1.11–1.54] and 1.90-fold in hACs [95% CI: 1.56–2] and 1.67-fold in ANP32A protein levels after DMM surgery with IOX2 injections [95% CI: 1.33–2.08]). Wnt hyper-activation decreased ANP32A in chondrocytes in vitro (1.23-fold decrease [95% CI: 1.02–1.49]) and in mice (1.45-fold decrease after CHIR99021 injection [95% CI: 1.22–1.72] and 1.41-fold decrease in Frzb -knockout mice [95% CI: 1.00–1.96]). Hypoxia and Wnt modulated ataxia-telangiectasia mutated serine/threonine kinase ( ATM ), an ANP32A target gene, in hACs (1.89-fold increase [95% CI: 1.38–2.60] and 1.41-fold decrease [95% CI: 1.02–1.96]). Conclusions: Maintaining hypoxia and limiting Wnt activation sustain ANP32A and protect against osteoarthritis.